A Study of Factors Influencing the Choices of the Consumers for the Portrayal of Women in Advertising - Saxena, Kavita (Journal of Commerce and Trade, 2017)
The role of women has been changing over the years in various fields around the world like advertising, academics, politics, etc. Today 30 per cent of employees in the software industry are women. Advertising has evolved into a powerful marketing tool over the last century. Advertising is one of the “promotional tools” used in marketing endeavors, as one means of communication between the seller (advertiser) and the buyer (consumer or organization). Advertising plays a very important role in communicating with the consumer and influencing the consumer's decision-making process. The general roles that women play in advertising are Decorative Role, Recreational Role, Independent Career Role, Self-involved Role, Carefree Role and Family Role. The portrayal of women in advertising has been particularly stereotypical with confinement of women to household chores. The female model in the advertisement or commercial should represent an image that target consumers can identify with. The aim of marketing communication is therefore to link the organization (sponsor) with the target audience in a manner to which the audience can relate. JEL Classification : D 11, J 16, M 37.